THE REPRESENTATION OF OBJECTS FUNCTION IN ANTI CORRUPTION COMMERCIAL VIDEO BASED ON PEIRCE’S SEMIOTICS - Fauziyah, Dalfa; Sakinah, R. Myrna Nur (UC Journal: ELT, Linguistics and Literature Journal, 2025)
This research analyzes signs in the Anti-Corruption (Commercial Video)-Final Year Project uploaded by Muiz Hr, with a duration of 2 minutes and 9 seconds and 14 thousand viewers. A qualitative method was used to explore the visual meanings in the video based on Charles Sanders Peirce's semiotic theory. Primary data was obtained through random sampling from YouTube, while secondary data was sourced from literature related to semiotics and anti-corruption campaigns. The analysis focused on identifying icons, indexes, and symbols in five selected key scenes. The results of the study show a total of 9 icons, 5 indexes, and 5 symbols that were analyzed based on Peirce’s object-function theory. The combination of these signs proved effective in conveying an anti-corruption message. Icons provide real-life visualizations such as everyday social interactions, indexes reveal causal relationships with corrupt actions, and symbols reinforce the moral message through text and objects. The overall interpretation indicates that the video successfully raises audience awareness about the dangers of corruption, emphasizing that corruption can occur anywhere and anytime, thus requiring vigilance and preventive actions from society.